Prevalence of neurocognitive disorder in Huntington’s disease using the Enroll-HD dataset - Sierra, Luis A.; Ullman, Clementina J.; Baselga-Garriga, Clara; Pandeya, Sarbesh R.; Frank, Samuel A.; Laganiere, Simon (Frontiers in Neurology, 2023)
Background Cognitive decline in Huntington’s disease (HD) begins early in the disease course, however the reported prevalence and severity of cognitive impairment varies based on diagnostic approach. A Movement Disorders Society Task Force recently endorsed the use of standardized DSM-5-based criteria to diagnose neurocognitive disorder (NCD) in Huntington’s disease. Objectives To determine the prevalence and severity of cognitive impairment across different stages of HD by applying NCD criteria (mild and major) to participant data from the Enroll-HD database. Methods Enroll-HD participants were triaged into either premanifest (preHD), manifest or control groups. PreHD was further dichotomized into preHD near or preHD far based on predicted time to diagnosis using the scaled CAG-age product score (CAPs). Embedded cognitive performance and functional independence measures were used to determine prevalence of NCD (mild and major) for all groups. Results Prevalence of NCD-mild was 25.2%–38.4% for manifest HD, 22.8%–47.3% for preHD near, 11.5%–25.1% for preHD far, and 8.8%–19.1% for controls. Prevalence of NCD-major was 21.1%–57.7% for manifest HD, 0.5%–16.3% for preHD near, 0.0%–4.5% for preHD far, and 0.0%–3.0% for controls. Conclusion The prevalence of NCD in HD is elevated in preHD and demonstrates a sharp rise prior to diagnosis. In manifest HD, the vast majority of participants meet criteria for NCD. These findings are important for optimizing clinical care and/or anticipating the need for supportive services.